2019
DOI: 10.1002/app.48716
|View full text |Cite
|
Sign up to set email alerts
|

WPU/CB/GO nanocomposites: in situ polymerization preparation, thermal, and anticorrosion performance evaluation

Abstract: In this paper, composite fillers including graphene oxide and carbon black had been applied to modify pure waterborne polyurethane (WPU) and a new nanocomposite was prepared by in situ polymerization, whose structure was characterized by Fourier transform infrared spectroscopy that demonstrated interfacial interactions existing between the filler particles and the hard segments of WPU chains. Meanwhile, thermal properties of prepared nanocomposites were enhanced after adding composite fillers as shown in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Hou and colleagues reported the preparation of nanocomposites based on waterborne polyurethane (WPU) as a polymer matrix and combination of graphene oxide (GO) and carbon black (CB) as nanomaterials [36]. First of all, the mixture of monomer (isophorone diisocyanate) and polypropylene glycol was stirred in a container at 85 °C for 3 h. Then, mixture of NMP/DMPA along with the few drops of dibutyltin dilaurate was incorporated into the system under stirring for 2 h, to obtain NCO-terminated prepolymer.…”
Section: In Situ Polymerizationmentioning
confidence: 99%
“…Hou and colleagues reported the preparation of nanocomposites based on waterborne polyurethane (WPU) as a polymer matrix and combination of graphene oxide (GO) and carbon black (CB) as nanomaterials [36]. First of all, the mixture of monomer (isophorone diisocyanate) and polypropylene glycol was stirred in a container at 85 °C for 3 h. Then, mixture of NMP/DMPA along with the few drops of dibutyltin dilaurate was incorporated into the system under stirring for 2 h, to obtain NCO-terminated prepolymer.…”
Section: In Situ Polymerizationmentioning
confidence: 99%
“…The physical blending [ 33 ] of GO or modified GO with dopamine and with WPU [ 34 ] can improve the mechanical properties and barrier properties of the coating [ 35 , 36 ]. However, physical blending will result in poor compatibility and dispersion of GO and WPU, and the modification ability of GO cannot be effectively exerted, which will easily cause stress concentration and get the opposite effect.…”
Section: Introductionmentioning
confidence: 99%
“…Yeh et al developed a WPU/Na+ -montmorillonite (Na+ -MMT) clay nanocomposite coating for practical evaluation of corrosion protection efficiency [ 9 ]. In 2019, Hou et al reported WPU nanocomposites with complex packing of GO and CB as anti-corrosive coating [ 10 ]. Liu et al proposed WPU nanocomposites with polyether-amine functionalized graphene oxide for anti-corrosion [ 11 ].…”
Section: Introductionmentioning
confidence: 99%